Marijuana in America: cultural, political, and medical controversies - Hawdon, James; Costello, Matthew; Miller, Bryan Lee (ABC-CLIO, an imprint of ABC-CLIO, LLC, 2022)
"This A-Z encyclopedia provides a broad and evenhanded overview of America's complex relationship with marijuana, examining political, recreational, cultural, medical, and economic aspects of marijuana use both historically and in the present day"--